2013
DOI: 10.1021/ja4057344
|View full text |Cite
|
Sign up to set email alerts
|

Threading Polyintercalators with Extremely Slow Dissociation Rates and Extended DNA Binding Sites

Abstract: The development of small molecules that bind DNA sequence specifically has the potential to modulate gene expression in a general way. One mode of DNA binding is intercalation, or the insertion of molecules between DNA base pairs. We have developed a modular polyintercalation system in which intercalating naphthalene diimide (NDI) units are connected by flexible linkers that alternate between the minor and major grooves of DNA when bound. We recently reported a threading tetraintercalator with a dissociation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Importantly, it was found that the chloro- and methoxy-groups in 1 could be replaced with a 2- or 4-carboxamido group (see 2 and 3 in Figure 1, respectively) without reducing its affinity for CUG repeats or its inhibition of the MBNL1·CUG complex. Although modeling was not carried out, it appeared that dimeric ligands interconnected at the 2- and 4-positions would have the linker and triaminotriazine recognition units located on the same or the opposite sides of the acridine unit, thereby likely requiring a non-threading or threading 54 mechanism of binding, respectively. This simple analysis suggested that these two isomeric dimers would significantly increase the diversity of our library, especially when considering the ultimate RNA-ligand complex.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, it was found that the chloro- and methoxy-groups in 1 could be replaced with a 2- or 4-carboxamido group (see 2 and 3 in Figure 1, respectively) without reducing its affinity for CUG repeats or its inhibition of the MBNL1·CUG complex. Although modeling was not carried out, it appeared that dimeric ligands interconnected at the 2- and 4-positions would have the linker and triaminotriazine recognition units located on the same or the opposite sides of the acridine unit, thereby likely requiring a non-threading or threading 54 mechanism of binding, respectively. This simple analysis suggested that these two isomeric dimers would significantly increase the diversity of our library, especially when considering the ultimate RNA-ligand complex.…”
Section: Resultsmentioning
confidence: 99%
“…Not mentioned here is our extensive work with DNA-binding oligo-NDI molecules. 74-76 Considering the complex nature of aromatic interactions, the predictable stacking geometry of DAN and NDI in water provides a well-defined recognition motif to achieve higher order architectures. Because the stacking of electrostatically complementary aromatic units is driven in part by polar solvents, the construction of aromatic foldamers and more complex aromatic assemblies in water can be more rationally designed.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, naphthalene diimides (NDI) with appropriate functionalization were found to be an excellent probe to intercalate with DNA double strands . Several detailed studies on NDI‐DNA interaction have been reported by Iverson and Wilson . A direct consequence of DNA‐binding by all these NDI derivatives is the drastic fall in fluorescence quantum yield of NDIs .…”
Section: Methodsmentioning
confidence: 99%
“…Several detailed studies on NDI‐DNA interaction have been reported by Iverson and Wilson . A direct consequence of DNA‐binding by all these NDI derivatives is the drastic fall in fluorescence quantum yield of NDIs . We envisioned that this quenching of emission upon binding with DNA can be utilized to create new sensor for proteins capable of binding with DNA, such as histone.…”
Section: Methodsmentioning
confidence: 99%